Differential Expression of Heat Shock Protein (HSP) 70-2 Gene Polymorphism in Benign and Malignant Pancreatic Disorders and Its Relationship with Disease Severity and Complications - Srivastava, Puja; Shafiq, Nusrat; Bhasin, Deepak Kumar; Rana, Surinder Singh; Pandhi, Promila; Behera, Arunanshu; Kapoor, Rakesh; Malhotra, Samir; Gupta, Rajesh (JOP. Journal of the Pancreas, 2012)
Context The role of heat shock protein (HSP) 70-2 gene polymorphism (at position 1267, A to G transition) in patients with pancreatic disorders is not clear. Objective To evaluate HSP 70-2 gene polymorphism (at position 1267, A to G transition) in patients with acute and chronic pancreatitis as well as pancreatic carcinoma, and to find any association of this polymorphism with disease complications and severity. Methods One-hundred and fifty patients (50 each of acute, chronic pancreatitis, and pancreatic carcinoma) and 50 healthy blood donors as controls were prospectively studied. Three alleles (AA, AG and GG) of HSP 70-2 gene determined by PstI restriction fragment length polymorphism. Results There was a statistically significant difference in the distribution pattern of HSP 70-2 gene polymorphism in patients with acute pancreatitis (P=0.001) and pancreatic carcinoma (P<0.001) as compared to controls. The frequency of mutant allele (G allele) was significantly higher in diseased group as compared to control group (19% in control group, 40% in acute pancreatitis, 33% in chronic pancreatitis and 45% in pancreatic carcinoma). No association of this polymorphism was found with disease severity in patients with acute and chronic pancreatitis or pancreatic carcinoma. Conclusions In our patient sample the frequency of mutant allele (G allele) of HSP 70-2 gene is significantly higher in patients with acute pancreatitis and pancreatic carcinoma compared to controls (50 healthy blood donors). However, this polymorphism was not associated with disease severity and complications. Image: Allelic distribution in the study population.